What a Bad Dog - Hunt, Roderick, 2012; Roderick Hunt, 1986; Alex Brychta, 1986 (UK Oxford reading press, 2012)
In this story, the children$1 (Bs dog, Floppy, keeps getting into trouble. He makes a mess in the house, steals food, and doesn$1 (Bt listen. Everyone says, (3z(BWhat a bad dog!(3y (BBut in the end, Floppy surprises everyone by being very brave and helpful$1 (Bhe saves the day! The family realizes Floppy isn$1 (Bt such a bad dog after all.s
Oxford Reading Tree (ORT) Stage 2 book "What a Bad Dog!" that can be used for guided reading or library sessions.
H3
It is classified as a Stage 2 reader in the ORT series, which aligns with children who are just beginning to read independently. These books feature: Simple sentence structures. Repetitive and predictable language. Strong visual support through illustrations. The story features familiar characters (like Kipper and Floppy the dog), making it engaging for young learners just starting their reading journey.
Keywords: Supplementary reading material